Cardiorenal prognosis by residual proteinuria level in diabetic chronic kidney disease: pooled analysis of four cohort studies. Issue 11 (2nd March 2018) - Minutolo, Roberto; Gabbai, Francis B; Provenzano, Michele; Chiodini, Paolo; Borrelli, Silvio; Garofalo, Carlo; Sasso, Ferdinando C; Santoro, Domenico; Bellizzi, Vincenzo; Conte, Giuseppe; De Nicola, Luca
Abstract: Background: No study has assessed whether the prognosis of coexisting diabetes mellitus and chronic kidney disease (DM-CKD) is dictated by DM per se or by the extent of proteinuria. Methods: In this pooled analysis of four prospective studies in CKD patients treated with drugs inhibiting the renin–angiotensin system, we compared the risk of all-cause mortality, fatal and non-fatal cardiovascular (CV) events and end-stage renal disease (ESRD) between patients with ( n = 693) and without diabetes ( n = 1481) stratified by proteinuria level (<0.15, 0.15–0.49, 0.5–1 and >1 g/day). Results: The group with DM-CKD was older (69 ± 11 versus 65 ± 15 years), had a higher body mass index (29.6 ± 5.4 versus 27.5 ± 4.8 kg/m 2 ) and systolic blood pressure (143 ± 19 versus 136 ± 18 mmHg), prevalent CV disease (48% versus 29%) and lower estimated glomerular filtration rate (34.5 ± 17.9 versus 36.6 ± 19.0 mL/min/1.73 m 2 ). During 4.07 years of follow-up, there were 466 patients with ESRD, 334 deaths and 401 CV events occurred. In the subgroup with urine protein <0.15 g/day ( N = 662), the risks of ESRD, CV events and mortality were similar in diabetic and non-diabetic patients. Conversely, in DM-CKD patients, the mortality risk was higher in proteinuric patients hazard ratio 1.92 [95% confidence interval (CI) 1.25–2.95); 1.99 (1.26–3.15) and 1.98 (1.28–3.06) for proteinuria 0.15–0.49, 0.5–1 and >1 g/day, respectively, whereas in non-diabetics the mortality risk increased only for proteinuria 0.5–1 g/day [HR 1.60 (95% CI 1.07–2.40)] and >1 g/day [HR 1.69 (95% CI1.20–2.55)]. In both groups, CV risk had a trend similar to that of mortality. ESRD risk increased progressively across strata >0.5 g/day independent of diabetic status. Conclusions: We provide evidence that patients with non-proteinuric DM-CKD are not exposed to higher cardiorenal risk. In contrast, in the presence of moderate proteinuria and diabetes per se is associated with a higher risk of mortality and CV events, whereas the entity of abnormal proteinuria modulates ESRD risk independent of diabetes.